Membranoproliferative glomerulonephritis in sibs - Söylemezoğlu, Oğuz; Tınaztepe, Keriman; Bakkaloğlu, Ayşın; Saatçi, Ümit (The Turkish Journal of Pediatrics, 1992)
Idiopathic membranoproliferative glomerulonephritis (MPGN) is a chronic renal disease with variable clinical expression and several distinct morphological subtypes. Two sibs, aged 10 and 13, presented with clinical and laboratory findings of MPGN at the time of admission. After an interval of one year, the diagnosis of MPGN was established by renal biopsies. The complement pathway was unremarkable. HLA typing in the unrelated parents and the two male sibs revealed common HLA A2,A11,Bw60, DR2,DQw1 antigens in the brothers. Of these antigens, A2 has been reported previously in cases of MPGN. The other antigens regarding this disease need to be evaluated from the standpoint of genetic importance.